Improving Learning Outcomes Passing and Control in a Football Game Through Learning Models Problem Based Learning in Class XI Students West Seram State High School 16 - Teapon, Sunarti; Hasbullah, Bahmid; Moh. Latar, Idris (Peneliti.net, 2024)
Looking at the identification results, it can be explained that students are not yet able to carry out basic passing and control techniques properly and correctly. Due to the use of inadequate media and facilities, and the learning method used by the teacher is the conventional method (lecture method). This research uses the Problem Based Learning learning model to improve learning outcomes in passing and control in the game of soccer using the Problem Based Learning learning model for students at SMA Negeri 16 Seram Barat. Data obtained through Classroom Action Research (PTK) was carried out in two cycles, namely cycle I and cycle II. Data for each cycle is obtained from the results of observations and performance tests based on indicators assessed by the assessment rubik. This score is the final result obtained by each student which will determine whether this student is declared complete or not so that it can be continued in cycle II. Student learning outcomes can be seen in the results of students' ability tests during cycle II, namely in cycle I obtained 77% and in cycle II obtained 90% completeness, there was an increase of 13% in the use of the Problem Based Learning learning model carried out by teachers from cycle I to cycle II. This shows the teacher's success in managing or facilitating the learning process.